Impact of estrogen on IgG glycosylation and serum protein glycosylation in a murine model of healthy postmenopause - Gupta, Priti; Sághy, Tibor; Nordqvist, Jauquline; Nilsson, Jonas; Carlsten, Hans; Horkeby, Karin; Henning, Petra; Engdahl, Cecilia (Frontiers in Endocrinology, 2023)
Introduction: The glycosylation of immunoglobulin (Ig) G regulates IgG interaction capability with Fc gamma receptors found in all immune cells. In pathogenic conditions, estrogen can impact IgG levels and glycosylation. Following menopause, when estrogen levels decline affecting the immune system and potentially leading to a heightened susceptibility of immune activation. Purpose: In this study, we aim to determine if estrogen levels can regulate IgG glycosylation in postmenopausal healthy situations. Methods: Mice were ovariectomized to simulate an estrogen-deficient postmenopausal status and then treated with 17-beta-estradiol (E2) at different doses and different administration strategies. Results: Using a highly sensitive liquid chromatography-tandem mass spectrometry (MS/MS) glycoproteomic method, we demonstrated that E2 treatment increased the degree of glycosylation on IgG-Fc with both galactosylation and sialylation in the position required for interaction with Fc gamma receptors. We also observed that only long-term estrogen deficiency reduces IgG levels and that estrogen status had no impact on total IgG sialylation on both Fab and Fc domains or general glycoprotein sialylation evaluated by ELISA. Furthermore, E2 status did not affect the total sialic acid content of total cells in lymphoid organs and neither B cells nor plasma cells. Conclusion: The study concluded that E2 treatment does not affect total serum glycoprotein sialylation but alters IgG glycosylation, including IgG sialylation, implying that estrogen functions as an intrinsic modulator of IgG sialylation and could thereby be one pathway by which estrogen modulates immunity.